The Growth of Entire Functions Defined by Laplace–Stieltjes Transforms Related to Proximate Order and Approximation - Wen Ju Tang; Jian Chen; Hong Yan Xu (Journal of Function Spaces)
In this article, we discuss the growth of entire functions represented by Laplace–Stieltjes transform converges on the whole complex plane and obtain some equivalence conditions about proximate growth of Laplace–Stieltjes transforms with finite order and infinite order. In addition, we also investigate the approximation of Laplace–Stieltjes transform with the proximate order and obtain some results containing the proximate growth order, the error, An∗, and λn, which are the extension and improvement of the previous theorems given by Luo and Kong and Singhal and Srivastava.